Faktor Determinan Kondisi Kaki Pasien Diaetes Mellitus - Sanny Frisca (Faletehan Health Journal, 2023)
Diabetes mellitus (DM) is a chronic disease that can lead hyperglicemia condition. Hyperglicemia can cause macrovasculer, microvascular, and neurophaty diseases which lead to foot disease. To prevent it, patients need knowledge and practice of foot care. This study aimed to find factors that contribute to patient’s knowledge and foot condition. The data were collected by a questionnaire to assess patient’s knowledge and an observation checklist to assess patient’s foot condition. The bivariate analysis used Kendall Tau test and ordinal regression for multivariate. This study had 30 respondents with characteristic of pre-elderly age (56.7%), graduating from high school (76.7%), living with DM <1 year (53.3%), hyperglicemia (53.3%), low in knowledge (73.3%), and having a bad foot condition (73.3%). The results showed that respondents’ characteristics have no significant correlation to knowledge and foot condition. The analysis results of Kendall Tau test showed that hyperglicemia (τ=0.409; p=0.012) and patients’ knowledge (τ=0.480; p=0.015) significantly related to foot condition. Hyperglicemia and patients’ knowledge became predictor of foot condition with determinant coefision of 39.5%. Thus, if patients have a good knowledge and do not have hyperglicemia, they will achive a good foot condition. Therefore, education about foot care and how to stabilize blood sugar to the patients is necessary for further study.